FROM SCROLL TO SKILL: ENHANCING GEN Z'S SPEAKING SKILLS THROUGH TIKTOK CONTENTS - Gracelyne Chandra (English Language Teaching Prima Journal (ELT), 2025)
This study explored the use of TikTok as an informal learning platform to support Generation Z English as a Foreign Language (EFL) learners in improving their English speaking skills. A qualitative descriptive method was applied, involving 20 Gen-Z EFL learners selected through purposive sampling. Data were collected over an eight-week period using semi-structured interviews, observations, and analysis of learner TikTok video testimonies. The findings indicated that learners perceived TikTok as an engaging, accessible, and motivating platform that contributed to improvements in pronunciation, vocabulary use, fluency, and speaking confidence. Learners frequently engaged with content such as pronunciation tutorials, daily conversation expressions, and short vocabulary lessons, which encouraged repeated exposure and self-directed speaking practice. Despite these advantages, the study also identified several challenges, including distractions, limited depth of explanations, and the presence of unreliable learning content. These issues suggest that learners require adequate digital literacy and strategic guidance to maximize the educational benefits of TikTok. Overall, TikTok was found to be a supportive tool for developing speaking skills when used intentionally, although it is best utilized as a supplementary resource alongside formal English instruction.